Skazani na uran. Kopalnie rudy uranu we wspomnieniach żołnierzy batalionów pracy - Klementowski, Robert (Wydawnictwo Uniwersytetu Wrocławskiego, 2009)
The creation of military Labor Battalions in Poland in 1949 was conditioned by economic needs, i.e. the deficit of employees in the mining industry. At the same time, however, because of the certain mode of conscripts’ selection, the Battalions became the part of the repressive system directed against individuals and circles who were deemed by the authorities to be hostile or opposed to communism. The Minister of National Defence Konstanty Rokossowski expressly indicated that “the basis to qualify a conscript to the replacement service [was] his social background, his political and moral persuasion and his political past”. That is how former Boy Scouts of “Szare Szeregi”, AK or NSZ soldiers, members of the Polish Armed Forces in the West and of Guard Companies in the American Army ended up in replacement military service. The soldiers of Labor Battalions were directed to coal mines and quarries. Two of those Battalions no. X and XI – together they formed X Labor Brigade found themselves mining uranium ore in Lower Silesia. Taken together, during one and the half years June 1950–November 1951 around 4000 soldiers served in the Brigade. They were working after a very brief training, mostly as loaders or carriers, in dismal conditions, without proper ventilation, in excessive dust, endangered by radiation. The disregard for any health-and-safety measures caused them to be a group constantly threatened by accidents. After working hours, confined to their barracks, in bad hygienic conditions, guarded by members of the Internal Security Corps, they were subject to political indoctrination, invigilation, and drill by Military Information. In 1994 the Polish Parliament recognized forced labor in BPs as a special kind of repression.
Keywords: kopalnie uranu; bataliony pracy; żołnierze; represje